Upgrade of SARAF fast beam chopper and its applications in Phase I and Phase II of SARAF linac. (1st November 2022) - Kaizer, B.; Shor, A.; Zchut, T.; Weissman, L.; Perry, A.; Kreisel, A.; Tessler, M.; Hirsh, T.; Farber, E.
Abstract: A fast chopper system has been developed for single-bunch selection for Phase I of the Soreq Applied Research Accelerator Facility (SARAF) in Israel. Further upgrade of the fast chopper system has improved its performance by enabling single-bunch selection for protons and deuterons at a repetition rate up to 220 kHz, with bunch transmission of up to 65% and with neighboring bunch contamination of less than 15%. The upgrade included (1) the redesign of the chopper deflection plates to minimize the electric-field asymmetry and provide more effective single-bunch selection, (2) a new trigger system with better trigger time resolution and better control capabilities, (3) an upgrade of the chopper electronics to increase the repetition rate, (4) the design of the chopper machine protection system, and (5) a general upgrade of the chopper concept to allow for operation in fast and slow modes. The implemented upgrades and the performance of the upgraded system are described. In addition, examples of the first experiments using the neutron time-of-flight (TOF) technique are presented. A fast neutron TOF facility, based on the upgraded fast chopper, is planned for SARAF Phase II. The high neutron flux at SARAF Phase II combined with the upgraded fast chopper system will make SARAF competitive with other advanced neutron research facilities.